Isolation and identification Klebsiella pneumoniae bacteria from different clinical sources of human in Al-Diwaniyah city - Nima, Mona; Syoof Khoman Al-Ramahi (Al-Qadisiyah Journal of Pure Science, 2020)
Gram negative bacteria pathogens are an important cause of hospital and community acquired infections all over the world. Klebsiella spp. particularly Klebsiella pneumoniae has become one of the more common cause of these infections and one of the important aspects of Klebsiella associated infections is undergoing a high rate of antibiotic resistance strains particularly those involved in nosocomial diseases due to development and alterations in the genome of it . This study included the isolation of Klebsiella pneumoniae bacteria from different clinical sources of human and identification through biochemical tests and VITEK 2-Compact system .The results presentation that Klebsiella pneumoniae were isolated and identified 55 (62.5%) Out of the1total number of (150) human patients. .The number of K. pneumonia isolates from burns and wounds was 6 (60%) ,urine samples 11(34.37%) sputum samples 32(80%) , and blood samples 6 (100 %). The results of the statistical analysis showed very significant differences indicating a higher level of Klebsiella pneumoniae in sputum